1998
DOI: 10.1104/pp.116.1.409
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Induces Oxidative Stress Genes in Arabidopsis thaliana1

Abstract: Changes in gene expression induced by toxic levels of Al were characterized to investigate the nature of Al stress. A cDNA library was constructed from Arabidopsis thaliana seedlings treated with Al for 2 h. We identified five cDNA clones that showed a transient induction of their mRNA levels, four cDNA clones that showed a longer induction period, and two down-regulated genes. Expression of the four long-term-induced genes remained at elevated levels for at least 48 h. The genes encoded peroxidase, glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
234
0
11

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(256 citation statements)
references
References 41 publications
11
234
0
11
Order By: Relevance
“…These have been reported as inducible by stresses such as high aluminium, fungal infection, and wounding (Cordero et al, 1994;Richards et al, 1998). With the same kinetics, ␤-glucosidases were found that catalyse the hydrolysis of 1,3-␤-D-glucosidic linkages in 1,3-␤-D-glucans.…”
Section: The Time-specific Response Of Transcripts In Pokkalimentioning
confidence: 68%
“…These have been reported as inducible by stresses such as high aluminium, fungal infection, and wounding (Cordero et al, 1994;Richards et al, 1998). With the same kinetics, ␤-glucosidases were found that catalyse the hydrolysis of 1,3-␤-D-glucosidic linkages in 1,3-␤-D-glucans.…”
Section: The Time-specific Response Of Transcripts In Pokkalimentioning
confidence: 68%
“…Two metalbinding proteins, CCH (copper chaperone) and BCB (blue copper-binding protein), are among the genes induced by O 3 . These genes were previously shown to be induced by acute O 3 exposure; BCB was induced within a 3-h exposure to 0.30 L L Ϫ1 O 3 (Richards et al, 1998) and CCH transcript levels increased by 30% after a 30-min exposure to 0.80 L L Ϫ1 O 3 (Himelblau et al, 1998). Metal-binding proteins may play an important role in metal remobilization during senescence.…”
Section: Similarities and Contrasts To Natural Senescencementioning
confidence: 99%
“…It has also been shown that low concentrations of Al are suffi cient to generate ROS and provoke oxidative stress in plants (Richards et al 1998, Yamamoto et al 2002. We have analysed the responses of key antioxidant enzymes that have been previously shown to respond to metal-induced oxidative stress in plants (Gratão et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Al was shown to enhance SOD mRNA levels in the root tips of Arabidopsis (Richards et al 1998), the roots and shoots of rice seedlings (Sharma & Dubey 2007) and the roots of sorghum (Peixoto et al 1999). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation